Type I Interferon Supports Inducible Nitric Oxide Synthase in Murine Hepatoma Cells and Hepatocytes and during Experimental Acetaminophen-Induced Liver Damage - Bachmann, Malte; Waibler, Zoe; Pleli, Thomas; Pfeilschifter, Josef; Mühl, Heiko (Frontiers in Immunology, 2017)
Cytokine regulation of high-output nitric oxide (NO) derived from inducible NO synthase (iNOS) is critically involved in inflammation biology and host defense. Herein, we set out to characterize the role of type I interferon (IFN) as potential regulator of hepatic iNOS in vitro and in vivo. In this regard, we identified in murine Hepa1-6 hepatoma cells a potent synergism between pro-inflammatory interleukin (IL-1)-b/tumor necrosis factor (TNF)-a and immunoregulatory IFNb as detected by analysis of iNOS expression and nitrite release. Upregulation of iNOS by IFNb coincided with enhanced binding of STAT1 to a regulatory region at the murine iNOS promoter known to support target gene expression in response to this signaling pathway. Synergistic iNOS induction under the influence of IFNb was confirmed in alternate murine Hepa56.1D hepatoma cells and primary hepatocytes. To assess iNOS regulation by type I IFN in vivo, murine acetaminophen-induced sterile liver inflammation was investigated. In this model of acute liver injury excessive necroinflammation drives iNOS expression in diverse liver cell types, among others hepatocytes. Herein, we demonstrate impaired iNOS expression in type I IFN receptor-deficient mice which associated with diminished acetaminophen (APAP)-induced liver damage. Data presented indicate a vital role of type I IFN within the inflamed liver for fine-tuning pathological processes such as overt iNOS expression.